High‐temperature Fe oxidation coupled with redistribution of framework cations in lobanovite, K2Na(Fe2+4Mg2Na)Ti2(Si4O12)2O2(OH)4 – the first titanosilicate case. Issue 4 (14th June 2019) - Zhitova, Elena S.; Zolotarev, Andrey A.; Hawthorne, Frank C.; Krivovichev, Sergey V.; Yakovenchuk, Viktor N.; Goncharov, Alexey G.
Abstract : High‐temperature study of lobanovite from a heterophyllosilicate family revealed that the mineral undergoes iron oxidation coupled with deprotonation (starting at T > 450°C) followed by rearrangement of Fe and Mg cations within close‐packed octahedral layers. Abstract : The high‐temperature (HT) behaviour of lobanovite, K2 Na(Fe 2+ 4 Mg2 Na)Ti2 (Si4 O12 )2 O2 (OH)4, was studied using in situ powder X‐ray diffraction in the temperature range 25–1000°C and ex situ single‐crystal X‐ray diffraction of 17 crystals quenched from different temperatures. HT iron oxidation associated with dehydroxylation starts at 450°C, similar to other ferrous‐hydroxy‐rich heterophyllosilicates such as astrophyllite and bafertisite. A prominent feature of lobanovite HT crystal chemistry is the redistribution of Fe and Mg+Mn cations over the M (2), M (3), M (4) sites of the octahedral (O ) layer that accompanies iron oxidation and dehydroxylation. This HT redistribution of cations has not been observed in titanosilicates until now, and seems to be triggered by the need to maintain bond strengths at the apical oxygen atom of the TiO5 pyramid in the heteropolyhedral (H ) layer during oxidation–dehydroxylation. Comparison of the HT behaviour of lobanovite with five‐coordinated Ti and astrophyllite with six‐coordinated Ti shows that the geometry of the Ti polyhedron plays a key role in the HT behaviour of heterophyllosilicates. The thermal expansion, geometrical changes and redistribution of site occupancies which occur in lobanovite under increasing temperature are reported. A brief discussion is given of minerals in which the cation ordering (usually for Fe and Mg) occurs together with iron oxidation–dehydroxylation at elevated temperatures: micas, amphiboles and tourmalines. Now this list is expanded by the inclusion of titanosilicate minerals.